Analyze the trend of investment and trade between Lao PDR and China under the project "The Belt and Road" from 2021-2025 - SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; SONESAI, Khamsone; LAYASENG, Somyot; SOULISACK, Sithat (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The paper aims to study 1) the role of the Belt and Road in stimulating investment between Lao PDR and China from 2010-2020. 2) Role of the Belt and Road in stimulating trade between Lao PDR and China from 2010-2020. 3) Trends of investment and trade between Lao PDR and China under the "The Belt and Road" project from 2021-2025. As we acknowledge that "The Belt and Road" is one of the most robust firm’s foreign policy, economy, investment, trade and culture to diplomatic practices. The results of the study show that the current investment of China in Laos volume increased steadily, which has become an attractive foreign largest number 1. Notice the value investment, but over the years 2010-2020 amounts accumulated up to 12,812,822,029 US dollars, for investment in China emphasis Sector is construction sector and electric power sectors. The trade between China and Lao PDR shows that during the period of 2010-2020, China and Lao PDR have both encouraged and encouraged the two countries' good trade ties with good prospects to continue to grow and become good partners, with the imports value of goods and services from China from 2010-2020 to 8,317,247,588.15 US dollars. The export value of goods and services of Laos to China each year 2010-2020 amounted to 9,173,547,133.58 US dollars. In addition, the results of the analysis of investment and trade trends between Lao PDR and China under the " The Belt and Road " from 2021-2025 show that the trend of Chinese investment value is stable at 1,164,802,002.64 US dollars per year, with a significant at 0.05. In 2025, the trade value is expected to reach 4,724,677,938.20 US dollars with a significant at 0.05.